Health Expenditure Growth: Looking beyond the Average through Decomposition of the Full Distribution - Claudine de Meijer; Marc Koopmanschap; Owen O'Donnell; Eddy van Doorslaer (Tinbergen Institute, 2012)
Explanations of growth in health expenditures have restricted attention to the mean. We explain change throughout the distribution of expenditures, providing insight into how growth and its explanation differ along the distribution. We analyse Dutch data on actual health expenditures linked to hospital discharge and mortality registers. Full distribution decomposition delivers findings that would be overlooked by examination of changes in the mean alone. The growth in expenditures on hospital care is strongest at the middle of the distribution and is driven mainly by changes in the distributions of determinants. Pharmaceutical expenditures increase most at the top of the distribution and are mainly attributable to structural changes, including technological progress, making treatment of the highest cost cases even more expensive. Changes in hospital practice styles make the largest contribution of all determinants to increased spending not only on hospital care but also on pharmaceuticals, suggesting important spill over effects.
urn:NBN:nl:ui:15-1765/32666
Keywords: I10; 330; Health care expenditure; decomposition; aging; pharmaceuticals; the Netherlands; Gesundheitskosten; Alternde Bevölkerung; Niederlande